Patterns of dental caries following the cessation of water fluoridation - Maupome´ G, Clark DC, Levy SM, Berkowitz J. (Blackwell Synergy, 2001)
To compare prevalence and incidence of caries between fluoridation-ended and still-fluoridated communities in British Columbia, Canada, from a baseline survey and after three years. Methods: At the baseline (1993/4 academic year) and follow-up (1996/7) surveys, children were examined at their schools.